Simultaneously Improving Flame Retardant Performance, Thermal Stability and Conductivity of Copolymers of Polyethylene‐octene by Addition of a Ternary Composite Flame Retardant System - Zhang, Yafeng; Yu, Chunming; Feng, Xi (ChemistrySelect (Weinheim), 2022)
The development of high efficiency and low‐cost refractories has always been a subject that attract people‘s attention. Although polyethylene‐octene copolymers (POE) has excellent mechanical properties, it is easy to be ignited, which seriously hinders its multi‐field applications. In this paper, a novel ternary composite flame retardant system, ammonium polyphosphate (APP)/expanded graphite (EG)/sepiolite (SEP), was proposed and applied to POE to prepare high flame‐retardant POE composites. The experimental results showed that the addition of SEP could play a good reinforcing role, so as to improve the mechanical properties of POE/APP composites. Thermogravimetric analysis (TGA) showed that when the ratio of EG and SEP was 1 : 1, the initial thermal decomposition temperature decreased significantly, which was conducive to the early degradation and carbonization of POE/APP composites. The thermal conductivity test showed that the addition of SEP can reduce the thermal conductivity of POE/APP composites. In addition, the flame retardant test results revealed that when the ratio of EG and SEP was 1 : 1, the oxygen index (LOI) increased to 25.3 %, the heat release rate (HRR) decreased to 140 kW/m2, the total heat release (THR) decreased to 70 MJ/m2, and the carbon layer produced by combustion was dense and uniform, which contribute to the great heat insulation. In conclusion, the addition of an appropriate amount of ternary compound flame retardant (EG/SEP/APP) could have an excellent synergistic flame retardant effect on POE/APP composites, and the processing method was simple and efficient, which would benefit to broad application of the prepared POE composites. The addition of an appropriate amount of ternary compound flame retardant (expanded graphite/sepiolite/ammonium polyphosphate) can effectively improve the flame retardancy of polyethylene‐octene (POE) composites such as increasing their oxygen index (LOI) and reducing their heat release rate (HRR) and total heat release (THR) and effectively improve the thermal stability and conductivity of POE composites, which greatly broadens their application in heat transfer materials.